Measurement Guidance of The Quality Cost of Hospital Services - Sunardi; Aprianto; M. Rezky Septiyadi; Wingki Sapta Dewa (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Assistance in measuring the cost of quality of hospital services is essential to find out how much quality of service is provided and the costs incurred, so that efficiency and patient safety are guaranteed. Elements of quality cost include: prevention costs, assessment costs, internal failure costs, and external failure costs. This activity was carried out at Muhammadiyah Hospital in Palembang. The calculation of quality costs had not been calculated, the expenditure for quality cost elements had been carried out by the finance department. The result of this assistance is the availability of quality cost measurement instruments to evaluate the quality of service and costs incurred so that in the end it can be realized that the higher the quality of service, the lower the costs incurred. Conclusion: this instrument can be used as an early warning system in quality cost expenditures in addition it can be used as evaluation material every month and year so that hospitals can grow and develop consistently